FT-IR and Raman Spectroscopic And DFT Theoretical Investigations On Zn(II) Halide Complexes Of 2-Aminopyrimidine - Akalın, Elif; AKYÜZ, SEVİM (Elsevier Science Bv, Po Box 211, 1000 Ae Amsterdam, Netherlands, 2010)
In this study the vibrational spectra of monomeric Zn(L)(2)X(2) (X = Cl and Br; L = C(4)H(5)N(3) = 2APM, 2-aminopyrimidine) compounds are reported and discussed. Full assignment of the spectra is presented and the analysis of the experimental data is supported by DFT calculations performed with B3LYP functional and the 6-311++G(d,p) basis set. The FT-IR (400-4000 cm(-1)) and Raman (100-3200 cm(-1)) spectra of compounds are recorded and compared with that of the calculated spectra. Anharmonic corrections to the harmonic wavenumbers are done with the same method and level of theory. The coordination effects on vibrational wavenumbers of 2APM are discussed in detail by comparing the spectra of free and coordinated 2APMs. The geometry optimization of [Zn(L)(2)X(2)] calculated using the DFT/B3LYP method with a 6-311++G(d,p) basis set yields a slightly distorted tetrahedral environment around Zn ion and compound reveals the C2 symmetry. The 2APM ligand is coordinated to Zn atom via ring nitrogen atom as monodentate ligand. The computed C-N bond length in Zn(2APM)(2)Br(2) complex is found to be slightly longer than the corresponding bond length in Zn(2APM)(2)Cl(2) complex. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: 2-Aminopyrimidine complexes; Zn(2APM)(2)Br(2); Zn(2APM)(2)Cl(2); Density functional theory; Anharmonic wavenumbers; Infrared spectrum; Raman spectrum; thermochemistry; pyrimidine; spectra; Yoğunluk fonksiyonel teorisi; harmonik olmayan dalgasayıları; Kızıl Ötesi spektrum; Raman tayfı; termokimya